HPLC analysis of phenolic compounds and flavonoids with overlapping peaks - Mizzi, Luke (Array, 2020)
The identification and quantification of phenolic compounds and flavonoids in various natural food products is typically conducted using HPLC analysis. Their analysis is particularly complex since most natural food products contain a large number of different phenolic compounds, many of which have similar chemical characteristics such as polarity, which makes complete separation of all eluents extremely difficult. In this work we present and validate a method for the quantitative determination of the concentration of two compounds with similar retention times, i.e. they show overlapping peaks in a mixed solution. Two pairs of phenolic compounds were investigated: caffeic and vanillic acids and ferulic and p-coumaric acids. This technique takes advantage of the different absorbances of the two phenolic compounds in the eluent at various wavelengths and can be used for the quantitative determination of the concentration of these compounds even if they are not separated in the HPLC column. The presented method could be used to interpret the results of HPLC analysis of food products which possess a vast spectrum of phenolic compounds and flavonoids.